Students’ Cultural and Economic Family Background and Duration of University Studies in Finland - Lehti, Hannu (Routledge, Taylor & Francis Group, 2025)
Applying a Bourdieusian perspective, we investigate whether families’ institutionalized cultural capital (parental education) and economic capital (family income) are associated with the duration of university studies in Finland. We use register data comprising 10,516 students enrolled in universities between 1999 and 2002 and Tobit modeling. The results do not entirely support our hypothesis Institutionalized cultural capital is not associated with students’ duration of university studies. However, having higher economic capital decreases the duration of university studies.